Stalemate at the Negotiations on Environmental Goods and Services at the Doha Round - Gaëlle Balineau; Jaime de Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
Pursuant to article 31 of the Doha mandate, WTO members have been asked to reduce or eliminate tariffs and NTBs on a list of Environmental Goods and Services (EGS) to be determined during the negotiations. This paper reviews progress so far. First, it reviews the identification process under the Committee on Trade and the Environment in Special Session (CTESS) since 2002, while discussing the difficulties in identifying EGS and the different approaches on the table. The paper then concentrates on tariff reductions and import responses that occurred since the start of the negotiations, focusing on the 26 products identified as "clear environmental goods".
Keywords: F18; Q56; 330